(untitled) - Roland de Vaux; (1903-1971) (U.S.A, 1978)
The author$1 (Bs intention is for this work to extend to three volumes. The present volume takes the people from their origins to their constitution as the (3z(Bpeople of Israel(3y (Bafter the settlement of the tribes in Canaan. The second volume will begin with the period of the Judges and go as far as the destruction of the kingdom of Judah. The last volume will include the history of the exilic and post-exilic periods and conclude with the conquest of Alexander the Great.s
Keywords: Jews -- History -- To 953 BC